The Politics and Economics of COVID-19 Relief in Times of Conflict and Vulnerability in the MENA Region - Diab, Jasmin Lilian; Fouad, Fouad (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
States throughout the MENA region have quickly reacted to contain the spread of the Coronavirus (COVID-19) in the region. With all necessary precautions at this developed stage of pandemic in place, the virus seems to be ‘contained’ to a large extent in the region thus far. The public health consequences have subsequently been ‘less severe’ than anticipated in a region tainted with its fair share of conflict and political and economic instability. Nonetheless, the pandemic is already the cause of dramatic economic, political and social consequences, in particular for the most vulnerable states and the most vulnerable factions of these states’ populations. A regional agenda of reform would assist in addressing the region’s structural imbalances and further assist with the design of a new inclusive growth model; however, the economic and political discrepancies in the region may serve as a fundamental hindrance to this process. The following piece will address regional responses amid these escalating realities as well as introduce potential policy recommendations across intersectional political, economic and health themes.